Training To Understand Bullying Material For Teenage Groups - Zulfakar (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Bullying is a harmful phenomenon of oppression, where individuals or groups with more power commit acts of violence against others with the intent to hurt. These actions can occur continuously and manifest in several forms, including physical, verbal, and relational bullying, as well as cyberbullying or bullying that occurs on social media. This phenomenon can occur in various environments, including schools, homes, and communities. In order to address this issue, community service activities aim to provide education and health training, especially to teenagers. This aims to enhance their understanding of the dangers of bullying as well as empower them to avoid such behavior so they can grow into responsible individuals and exhibit positive behavior in social interactions within the community. Implementation method: This community service activity was carried out in November 2024 in Mujur, Praya Timur District, Central Lombok Regency. FIPP-UNDIKMA lecturers acting as coordinators collaborated with the local village head to reach the target consisting of 30 teenagers and several elderly people. This activity includes providing educational training on understanding bullying material for the youth group using PowerPoint, followed by discussions and word-guessing games with the elderly. The results of this activity demonstrate the importance of nutrition education for the elderly, not only in increasing knowledge but also in changing behaviors that can reduce the risk of chronic diseases. Thus, this community service activity is considered very appropriate to meet the community's needs to prevent bullying issues in both community and school environments. In addition, the survey results show that 91% of the participants have understood the concept of bullying, which includes its definition, types, impacts, prevention methods, and reporting procedures. Thus, it can be concluded that this community service activity has successfully achieved its objectives and received positive responses from the participants, indicating that this activity is indeed a societal need to prevent bullying.